GROUP DYNAMICS IN VIRTUAL TEAMS: A SYSTEMATIC REVIEW OF COLLABORATION, CONFLICT, AND INNOVATION - Yohanes Wibisono; Shafira Widya Ramadhanti; Dina Maria Ulfa; Sopiah (RADJA PUBLIKA, 2025)
The shifting landscape of work due to digitalization has made virtual teams a primary organizational structure in global enterprises. However, group dynamics within such teams remain a challenge, particularly in terms of collaboration, conflict, and innovation. This study aims to examine the interrelationship among these three variables through a systematic review of 43 peer-reviewed journal articles indexed in Scopus over the past five years. Utilizing a Systematic Literature Review (SLR) approach based on the PRISMA protocol, the data were analyzed descriptively, thematically, and conceptually. The findings indicate that effective collaboration is influenced by work structure, trust, and leadership, while conflict plays a dual role as both an obstacle and a trigger for innovation. This review proposes a conceptual model titled the